Influence of skin-to-Skin Contact in Cesarean Birth on the Duration of Breastfeeding - الاحمد, هيفرون; احمد عبد الرحمن; حسن صالح (Latakia University Journal -Medical Sciences Series, 2024)
Objective: : To study the effect of early skin-to-skin contact between the mother and the newborn in the condition of a cesarean section and its relationship to the beginning and duration of breastfeeding. Patients and methods: A prospective cohort study. The research sample included 103 pregnant women with a singleton pregnancy and a gestational age of more than 37 weeks with an Apgar score at 5 minutes of more than 7 who were admitted and delivered in the obstetrics and gynecology department at Tishreen University Hospital in Lattakia during the time period April 2023-2024. the division according to the values ​​was made into two groups according to the presence or absence of a contact and the time of the contact began with follow-up of the results within 1 day,3,and 6 months. Results: There were statistically significant differences (p<0.05) between the study groups regarding the rate of breastfeeding. the rate of breastfeeding was higher in the contact group at the different time points of the study (day, 3, and 6 months) with results, respectively, (75% , 67.3% ,%50), compared to the non-contact group (52.9% , 41.2% , 33.3%). The breastfeeding rate was higher in the very early contact group (76.9 % , 69.2% ,53.8%) compared to the early contact group (73.1% , 65.4% , 46.1%) Conclusion: The breastfeeding rate was higher in the contact group compared to the non- contact group, with an advantage for the very early contact group.